Punishment in Islamic Criminal Law: Between Facts and Ideals of Punishment - Amin, Mahir; Candra, Marli; Nurmila Sari, Helga (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2024)
Punishment is a reaction to the crime. So, if a crime occurs, it will entitle the criminal to be punished, both from the social and legal perspectives. This study aims to see the interpretative dynamics of the provisions of legal sanctions with relaxation of punishment in Islamic criminal law, and how is the preference for positive legal sanctions and Islamic law in responding to justice amid the development of society's progress. This is anormative research based on library studies using a historical and comparative approach. This research is also strengthened by textual and context analysis of the criminal process that occurred in the early days of implementing Islamic criminal law, as well as sentencing practices in the history of Islamic criminal law. From the study and assessment carried out, the research states that in the application of criminal law, Islamic criminal law always considers the preferences of dynamic contextual compromises and ideal principles of Islam. The existence of this interplay arises from the existence of mitigating circumstances that allow other factors to be considered. Furthermore, there are various models of criminal sanctions imposed on perpetrators adjusted based on the place, time, and criminal individualization.